2019
DOI: 10.1177/1457496919832146
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence, Etiology, Treatment, and Outcomes of Pleural Infections in Adults Over a Decade in a Finnish University Hospital

Abstract: Background and Aims: The aim of the study was to ascertain changes in the incidence, etiology, treatment, and outcomes of pleural infections over a decade in a Finnish University Hospital. Materials and Methods: All patients treated for pleural infections in Tampere University Hospital during 2000–2008 and 2012–2016 were included. The incidence rates and the epidemiologic data and medical history of patients, etiology of infection, and treatment trends and outcomes were compared between the cohorts. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 25 publications
(34 reference statements)
0
22
0
3
Order By: Relevance
“…The incidence of pleural infection nearly doubled from the first to the second decade of the 21st century. 11,12,14 In Europe, the US, Canada, and Australia, 5,6,8,13,14,16 the average age of patients diagnosed with pleural infection is 58-63 years. However, a recent systematic review pointed out a discrepancy in the age bracket of adult patients with pleural infection between high-income and low(er)-income countries, where patients in the latter group tended to be 15 years younger on average.…”
Section: Epidemiologymentioning
confidence: 99%
“…The incidence of pleural infection nearly doubled from the first to the second decade of the 21st century. 11,12,14 In Europe, the US, Canada, and Australia, 5,6,8,13,14,16 the average age of patients diagnosed with pleural infection is 58-63 years. However, a recent systematic review pointed out a discrepancy in the age bracket of adult patients with pleural infection between high-income and low(er)-income countries, where patients in the latter group tended to be 15 years younger on average.…”
Section: Epidemiologymentioning
confidence: 99%
“…Reliable demographic or clinical features that indicate empyema associated with CAP have not emerged. 22 Pleural infection is roughly twice as prevalent in men, [11][12][13]15,[23][24][25] in patients with comorbidities (particularly diabetes mellitus, 23,24,[26][27][28][29][30][31] hypoalbuminemia, 7,8 and alcoholism). 7,8,26,32,33 However, the only independent variable associated with empyema (n ¼ 128) among 1,080 patients with invasive pneumococcal infection was the pneumococcal serotype (not any clinical or demographic features).…”
Section: General Principles Of Management Timely Identification Of Plmentioning
confidence: 99%
“…The crude and/or age-adjusted incidence of adult pleural infection is consistently rising in diverse cohorts and health systems (e.g., in Canada, 10,11 Denmark, 12 Finland, 13 and the United States). 14,15 The largest incidence ratio increase is in the elderly.…”
mentioning
confidence: 99%
“…Infections of the pleura are increasingly common and a substantial burden for health care as the disease often necessitates long hospitalization, lengthy antimicrobial regimens, pleural drainage, and even surgery (14). Most cases are related to pulmonary infections, but malignancies and other causes play a role as well (1).…”
Section: Introductionmentioning
confidence: 99%
“…Infections of the pleura are increasingly common and a substantial burden for health care as the disease often necessitates long hospitalization, lengthy antimicrobial regimens, pleural drainage, and even surgery (14). Most cases are related to pulmonary infections, but malignancies and other causes play a role as well (1). The overall long-term survival of these patients is impacted, and the authors have previously reported that the rate of cancer-related deaths was approximately twofold in these patients when compared with that of age- and gender-matched controls (5, 6).…”
Section: Introductionmentioning
confidence: 99%